Excessive Use of Mobile Phones and Social Networks Among Colombian University Students - Lis-Gutiérrez, Jenny Paola; Zapata-Patarroto, Henry (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Social networks facilitate interactions among individuals, organizations, and communities. Their usage, especially among young people, has become increasingly widespread. This surge in usage has been linked to various impacts on individuals’ daily lives and well-being, particularly in academic and emotional aspects. OBJECTIVES: This study seeks to examine the extent to which excessive use of social networks (SN) contributes to social isolation among undergraduate students aged 18 to 35, residing in the departments of Cundinamarca, Boyaca, and Meta in Colombia. This phenomenon is primarily due to problematic cell phone use. METHODS: We administered two established instruments: the "Mobile Phone Problem Use Scale (MPPUS-10)" adapted by Foerster et al. (2015), and the "Addiction to Social Networks Questionnaire " developed by Escurra & Salas (2014). Statistical analyses included descriptive techniques, multivariate Henze-Zirkler normality test, univariate Shapiro-Wilk test, as well as non-parametric methods such as Spearman’s correlation and the Kruskal-Wallis test. RESULTS: Key findings of this study include: (i) the identified intervention and mitigation strategies in the literature predominantly focus on prevention programs and family support with an emphasis on bolstering young people’s self-esteem; (ii) 15.46% of the sample exhibited problematic cell phone use, with 25.96% indicating high intensity of social network use; (iii) significant differences were observed in relation to age and geographic location, while gender and socio-economic stratum did not exhibit a statistically significant impact; (iv) the statistical analysis demonstrated a positive and significant relationship with the dimensions of the Escurra & Salas (2014) instrument, namely Interest in Social Media (ISM), concern about lack of control (LC), and Excessive use of SN (EU). CONCLUSION: The Mobile Phone Problem Use Scale (MPPUS-10) emerges as a concise and effective tool for identifying problematic cell phone use, and its association with excessive social network usage underscores the interconnectedness of these behaviours. This research sheds light on the prevalence of these issues among Colombian university students and provides valuable insights for targeted intervention and support strategies, emphasizing the importance of bolstering self-esteem in youth.